1994
DOI: 10.1103/physrevlett.73.3419
|View full text |Cite
|
Sign up to set email alerts
|

Non-Arrhenius Reorientation Kinetics for the B-H Complex in Si: Evidence for Thermally Assisted Tunneling

Abstract: The B-H complex in Si can be aligned by stress and reorients with an activation energy of roughly 0.2 eV. We combine new measurements of the reorientation kinetics of the B-H complex made by the stress-induced dichroism technique with previous internal friction results to show that the reorientation kinetics are non-Arrhenius.These results support Stoneham's suggestion [Phys. Rev. Lett. 63, 1027] that reorientation occurs by thermally assisted tunneling.We have also discovered the remarkable fact that the reor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 22 publications
3
20
2
Order By: Relevance
“…36 We want to compare this value with the reorientation barrier of H in the acceptor-hydrogen complexes in Si. Two defects, B-H and Al-H, were investigated and it was found that E a Ϸ 0.2 eV for the B-H complex, 26 whereas E a = 0.37 eV for hydrogen bound to Al. 27 Obviously, of these two complexes, it is Al-H that has to be compared with isolated hydrogen since Al and Si are next neighbors in the Periodic Table. Indeed, in this case, the activation barrier for hydrogen reorientation in the Al-H complex is only 20% off from E a of isolated hydrogen.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…36 We want to compare this value with the reorientation barrier of H in the acceptor-hydrogen complexes in Si. Two defects, B-H and Al-H, were investigated and it was found that E a Ϸ 0.2 eV for the B-H complex, 26 whereas E a = 0.37 eV for hydrogen bound to Al. 27 Obviously, of these two complexes, it is Al-H that has to be compared with isolated hydrogen since Al and Si are next neighbors in the Periodic Table. Indeed, in this case, the activation barrier for hydrogen reorientation in the Al-H complex is only 20% off from E a of isolated hydrogen.…”
Section: Discussionmentioning
confidence: 98%
“…An enhancement of the reorientation temperature with replacement of hydrogen by deuterium is observed for acceptor-hydrogen complexes in Si and is normally attributed to zero-point energy effects. 26 It follows from Fig. 3 that hydrogen motion in the Cu-H complex is thermally activated and tunneling is not a dominating mechanism resulting in the defect alignment under stress.…”
Section: Frommentioning
confidence: 96%
See 2 more Smart Citations
“…33 Recent work suggests that the B-H complex in Si reorients by a thermallyassisted tunneling mechanism. 34,35 We show in Sec. V that the Al-H complex can also be aligned by stress, but with a small stress coupling, and that it too exhibits thermally activated reorientation.…”
Section: Introductionmentioning
confidence: 98%